Bioinformatics Analysis Identifies Potential Ferroptosis Key Gene in Type 2 Diabetic Islet Dysfunction - Ye, Haowen; Wang, Ruxin; Wei, Jinjing; Wang, Ying; Zhang, Xiaofang; Wang, Lihong (Frontiers in Endocrinology, 2022)
Background: Insulin is the key hormone for regulation of blood glucose and normoglycaemia is maintained by the balanced interplay between insulin action and insulin secretion. Importantly, the normal pancreatic cell can adapt to changes in insulin action, a decrease in insulin action is accompanied by upregulation. Thus, islet β cells dysfunction (IBCD) is a cortical component in the pathogenesis of type 2 diabetic mellitus (T2DM). Ferroptosis is a newly identified iron-dependent form of oxidative cell death that relies on lipid peroxidation. Previous data have indicated that ferroptosis is involved in various disease, including cancer, neurodegenerative diseases and T2DM. However, the concrete effect and key mechanism of ferroptosis on IBCD remains unknown. This study was performed to screen potential ferroptosis key genes related to the IBCD to reveal unknown physiological and pathological process. Methods: Using bioinformatics analysis, the islet tissues transcriptome data of T2DM from Gene Expression Omnibus (GEO), ferroptosis-related genes (FRGs) from FerrDb database, Genecards database and two new researches about FRGs were analyzed to identify differentially expressed genes. Firstly, T2DM key genes were screened by combined differentially expressed analysis and WGCNA. Then, T2DM-FRGs were identified by taking the intersection between T2DM key genes and FRGs. Finally, T2DM-FRGs was validated in another T2DM dataset and the miRNAs regulated T2DM-FRGs were predicted by using four miRNA databases. Results: 89 T2DM key genes were identified between DEGs and WGCNA. Furthermore, 3 T2DM-FRGs were screened by taking the intersection of T2DM key genes and FRGs, namely ITGA6, MGST1 and ENO2. In addition, MGST1 and ENO2 were validated as the T2DM-FRGs by another T2DM islet issues dataset. Conclusion: We identified MGST1 and ENO2 may be the potential ferroptosis key genes of IBCD in T2DM.